2009
DOI: 10.1016/j.jus.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging detection of new HCCs in cirrhotic patients treated with different techniques: Comparison of conventional US, spiral CT, and 3-dimensional contrast-enhanced US with the Navigator technique (Nav 3D CEUS)

Abstract: Introduction: The commercially available Navigator system ª (Esaote, Italy) allows easy 3D reconstruction of a single 2D acquisition of contrast-enhanced US (CEUS) imaging of the whole liver (with volumetric correction provided by the electromagnetic device of the Navigator ª ). The aim of our study was to compare the efficacy of this panoramic technique (Nav 3D CEUS) with that of conventional US and spiral CT in the detection of new hepatic lesions in patients treated for hepatocellular carcinoma (HCC). Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies in the literature have shown the superiority of CT over ultrasound in certain screening situations [ 6 , 8 ]. In patients that had been previously treated for HCC, an article by Giangregorio et al showed that the sensitivity of conventional US was much lower than that of MDCT for the detection of new HCC nodules [ 18 ]. Another possibility is for MDCT to be used alternately with ultrasound every 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have shown the superiority of CT over ultrasound in certain screening situations [ 6 , 8 ]. In patients that had been previously treated for HCC, an article by Giangregorio et al showed that the sensitivity of conventional US was much lower than that of MDCT for the detection of new HCC nodules [ 18 ]. Another possibility is for MDCT to be used alternately with ultrasound every 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, 3D CEUS is more similar to MRI and CT, and further studies are needed to evaluate the improvement in spatial and temporal resolution provided by the recently introduced new electronic matrix probes. Despite lacking real-time features, 3D CEUS appears to be promising in the calculation of tumor volume, definition of spatial geometry, and in detecting new foci of HCC occurring in patients already treated by means of LRT [8,17,18].…”
Section: Discussionmentioning
confidence: 99%